Emerson's Tragic Serenity and Unamuno's Tragic Sense of Life. - Harris, Kenneth Marc (Essays in Literature)
The article presents a discussion of Ralph Waldo Emerson's tragic sense which are reflected in two criticisms "Emerson's Tragic Sense," by Stephen E. Whicher and "The House of Pain," by Newton Arvin. Both agreed that Emerson showed insensitivity to human suffering in his work though Whicher tried to explain it while Arvin tried to justify it. Though tragic sense was not defined, both critics referred to Miguel de Unamuno's "The Tragic Sense of Life in Men and Nations" to understand what the term means.